The social and administrative aspects of the sermons of the Prophet Mohammad historical study of the era of prophethood - Alaseeri, Abdul- Aziz Ibrahem (Journal of Humanities & Social Sciences, 2021)
One of the greatest sermons that were delivered and whose effects remain to this day are the sermons of the Prophet, for the sermons of the Prophet were of great importance in depicting the life of the Prophet’s society and its way of life, hence we hope that this study will contribute to uncovering the social and administrative aspects of the Prophet’s society through the sermons that The Prophet delivered it in different seasons, as these signs can be monitored in the prophetic speeches to form the image of society in the Prophet’s era, through knowledge of social aspects such as customs, traditions, clothing, and adornment. As well as in the type of foods, the way they were eaten, and the tools used in preparing, eating and storing foods, and what this study means is to present another social picture of what the community of prophecy was, in terms of social solidarity,The way people live in homes, all of this by quoting from the sermons of the Prophet touched, and it is also of great importance to present the sermons of the Prophet which dealt with the role of women and the family in building civil society, and what the research will reveal is the subtle aspects of the prophetic society that permeated many of the prophetic speeches, such as Talking about the classes of society, and about fun, sports and tanning.On the other hand, this study provided an idea about the administrative and financial situation during the era of the prophethood, by extracting this information from the Prophet’s sermons, such as talking about the emirate over regions, organizing sergeants and captains, and also monitoring household resources and banks, as the sermons of the Prophet- ﷺ-  showed something of the organizational aspects in State administration such as bureaus, post office, and calculator.
Keywords: social; administrative aspects; sermons; the Prophet Muhammad; may God bless him and grant him peace